Light and focused ion beam microscopy workflow for resin-embedded tissues - Merchant-Larios, Horacio; Giraldo-Gomez, David M.; Castro-Dominguez, Adriana; Marmolejo-Valencia, Alejandro (Frontiers in Cell and Developmental Biology, 2023)
Although the automated image acquisition with the focused ion beam scanning electron microscope (FIB-SEM) provides volume reconstructions, volume analysis of large samples remains challenging. Here, we present a workflow that combines a modified sample protocol of the classical transmission electron microscope with FIB-SEM volume imaging. The proposed workflow enables efficient 3D structural surveys of rabbit ovaries collected at consecutive developmental stages. The precise trimming of the region of interest adds the time dimension to the volume, constructing a virtual 4D electron microscopy. We found filopodia-like processes emitted by oocyte cysts allowing contact between oocytes not previously observed.